Mechanika kwantowa a zdrowy rozsądek - Łukasik, Andrzej (Filozofia Nauki, 2010)
Quantum mechanics implies many paradoxes (e.g. Schrödinger's cat, double-slit experiment, non-locality) which are in contradiction to our ordinary experience. To comprehend quantum theory we must revise our understanding of such matters as the objective nature of reality, the nature of causality, and the nature of a complex system and its relation to its components. Finally, common sense seems to be an epistemo-logical obstacle in our understanding of the quantum picture of the world.